Economic basis of evaluation of land resources and their capitalization - Ugli , Мahsudov Muhammadbek Dilshodbek; Qizi, Bobomurodova Shokhsanam Shavkat (Goodwood Publishing, 2019)
Purpose: This article covers the issues of land resources evaluation and development of proposed recommendations in improving the processes of capitalization, examining the economic foundations of their capitalization. Research Methodology: Land valuation is of significant economic and social importance. From its data, it is widely used in solving various issues of economic sectors, including land tax, determining the amounts of rent on land plots, planning the yields of agricultural crops, creating land and in general, solving all issues that are closely related to land use. Results: New methods of capitalizing on land use have been proposed. Limitations: Capitalization issues are carried out on the basis of decisions of the executive power. In the introduction of experiments into practice, government decisions are relied on. Contribution: Modern methods of assessing land resources lead to sustainable economic growth. Keywords: Land resources, Valuation, Rent, Capital, Privatization